A retrospective study of functionality of patients with distal radius fracture after osteosynthesis with an LCP volar plate - Clé, Paula Guaraldo Villa; Tasso, Luiz Eduardo; Barbosa, Rafael Inácio; Fonseca, Marisa de Cássia Registro; Elui, Valéria Meirelles Carril; Roncaglia, Frederico Balbão; Mazzer, Nilton; Barbieri, Cláudio Henrique (Acta Fisiátrica, 2011)
Distal radius fractures are the most common fractures of the human skeleton, accounting for one sixth of all fractures. For his treatment, there are several surgical techniques and synthesizing materials that can be used, however, the use of a volar plate has been proven effective and haspresented few complications. Objective: Here was to make a retrospective study of thefunctionality of patients with distal radius fracture after internal fixation with an LCP volar plate that went through a rehabilitation program. Method: The sample consisted of 14 patients with unilateral distal radius fracture who underwent internal fixation with a 2.4 mm or 3.5 mm LCP volar plate who completed 1 year after surgery in 2010. The subjects were divided into two groups: affected group (n = 14), composed of fractured wrists; control group (n = 14) composed of the contralateral wrists. Measurements were made of active and passive range of motion (ROM) of the wrist, grip strength, pinch grip strength, and a questionnaire of disabilities of the arm, shoulder, and hand (DASH). The data was analyzed to compare the affected and controlgroups, through tests of significance of two independent samples for means. Results: The average for the DASH questionnaire was 10.63 points (± 12.23). For measures of grip strength, pinch grip strength, and ROM, there were no significant differences in comparison groups (p > 0.05). Conclusion: We concluded that after one year post-surgery, patients showed similar results when comparing the wrists, which shows a satisfactory recovery of functional status.